Kaposi’s sarcoma-associated herpesvirus ORF34 is essential for late gene expression and virus production - Mayu Nishimura (Nature Portfolio, 2017)
Abstract Kaposi’s sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi’s sarcoma, primary effusion lymphoma, and multicentric Castleman’s disease. KSHV establishes a life-long infection in its host and alternates between a latent and lytic infection state. During lytic infection, lytic-related genes are expressed in a temporal manner and categorized as immediate early, early, and late gene transcripts. ORF34 is an early-late gene that interacts with several viral transcription-associated factors, however its physiological importance remains poorly understood. Here, we investigated the role of ORF34 during KSHV infection by generating ORF34-deficient KSHV, using a bacterial artificial chromosome system. Our results reveal that ORF34-deficient KSHV exhibited significantly attenuated late gene expression and viral production but did not affect viral DNA replication. ORF34 interacted with transcription factors ORF18, ORF24, ORF31, and ORF66, and a novel ORF34-interaction partner, ORF23. The C-terminal region of ORF34 was important for interaction with ORF24 and viral production. Our data support a model, in which ORF34 serves as a hub for recruiting a viral transcription complex to ORF24 to promote late viral gene expression.